2018
DOI: 10.1186/s13104-018-3564-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT activity leads to the diagnosis of unsuspected TB: a retrospective study

Abstract: ObjectiveMycobacterium tuberculosis infection leads to latent or active tuberculosis (TB). Increased uptake on 18F-fluoro-2-deoxy-glucose-positron emission tomography/computed tomography (FDG-PET/CT) has been reported in the lungs and lymph nodes of individuals with recent infection and active TB, but not in individuals without known recent exposure or suggestive symptoms. We describe five patients with lung nodules not suspected to be due to TB in whom abnormalities on FDG-PET/CT scans ultimately were attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Much more recently, investigations such as positron emission tomography with concurrent computerized tomography that is able to detect, locate, and quantify neoplastic and inflammatory activity with increasing accuracy have been used to study metabolic activity in the mediastinal lymph nodes in individuals with probable persistent TB infection and have demonstrated activity in suspicious circumstances [56-58]. Other investigators using real-time polymerase chain reaction and immunochemistry have documented the presence of considerable amounts of M. tuberculosis constituents in these calcified lymph node lesions [59].…”
Section: Discussionmentioning
confidence: 99%
“…Much more recently, investigations such as positron emission tomography with concurrent computerized tomography that is able to detect, locate, and quantify neoplastic and inflammatory activity with increasing accuracy have been used to study metabolic activity in the mediastinal lymph nodes in individuals with probable persistent TB infection and have demonstrated activity in suspicious circumstances [56-58]. Other investigators using real-time polymerase chain reaction and immunochemistry have documented the presence of considerable amounts of M. tuberculosis constituents in these calcified lymph node lesions [59].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SUVmax has been shown to be a sensitive and accurate marker for noninvasive evaluation of treatment response, thereby indirectly prompting early diagnosis of resistant Mycobacterium tuberculosis strains [ 2 , 3 ]. Finally, a recent study evaluating asymptomatic patients with high SUVmax lesions provided new insights in the TB latency period [ 4 ]. It is worthy to remember, however, that no discriminative SUVmax value exists able to differentiate active TB from other malignant or infectious lesions [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only animal studies in non-human primate models were eligible for inclusion; all other animal studies reviewed involved rapidly progressive infection without a defined latent phase. In total, six studies met eligibility criteria for inclusion -two studies were experimental, prospective non-human primate studies [15,16] and four studies were in humans, including three retrospective [17][18][19] and one prospective cohort study [20] (Table 2). Collectively, these studies reported on four areas for review: i. cross-sectional PET-CT features of TBI (all six studies) [15][16][17][18][19][20]; ii.…”
Section: Study Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Collectively, these studies reported on four areas for review: i. cross-sectional PET-CT features of TBI (all six studies) [15][16][17][18][19][20]; ii. differences between TBI and active TB disease (two studies) [18,19]; iii. serial PET-CT features of progressive TBI (two studies) [15,16]; and iv.…”
Section: Study Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%